Implementasi Kebijakan Penyusunan Daftar Pemilih Pemilu 2024 di Kota Tangerang Selatan - Wahid Megantoro; Aditya Perdana (Jurnal Syntax Admiration, 2024)
The voter list in each election certainly has a degree of change for the better with the aim of having an accurate, comprehensive and up-to-date voter list. However, problems in the preparation of voter lists still continue to occur in the 2024 election. The purpose of this study is to find out the Implementation of the 2024 Election Voter List Preparation Policy in South Tangerang City. This study uses a qualitative method with a case study model. The results of this study show that the wider the degree of change expected and the many interests and strategies of the actors involved are obstacles to the success of a policy. On the other hand, the relationship between actors in the context of policy is an important factor in the success of policy. The lack of relationships between actors is a determinant factor in the occurrence of conflicts between the actors involved. The lower the relationship between the actors involved makes it difficult to implement policies.